ANALISIS MINAT UNTUK BERGABUNG DALAM KOPERASI PLASMA SRIBU KUBAH DI KEC. PADAMARAN, KAB. ROKAN HILIR, RIAU - Pasaribu, Yosua; Suranta Karo Sekali, Abednego (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
The core plasma partnership is regulated in PP RI No. 44 of 1997 concerning Plantations and the objectives of this government regulation, among other things, s to increase the country's foreign exchange sources, people's prosperity, and welfare, business opportunities and as well as creating jobs. However, plasma core partnerships are not appropriate. On the one hand, this kind of partnership can help oil palm farmers develop their economic and social sectors. On the other hand, there are doubts and dilemmas among farmers regarding joining cooperatives, which manifest in issues such as disputes over the use of funds and late payments. This shows the need to analyze more deeply the factors that influence farmers' interest in joining the Sribu Kubah plasma cooperative. This research uses Ajzen's Theory of Planned Behavior to understand farmers' attitudes and behavior in making decisions to join a cooperative. Variables such as Word of Mouth, perceived benefits, subjective norms, attitudes, and perceived behavioral control will be analyzed to identify the main factors influencing their decisions. So there are 3 variables that influence the Intention variable. These three variables are Perceived Behavioral Control, Subjective Norms, Word Of Mouth variables. This can be seen from the processed data by looking at the t value (1.96) and p value (0.05). The results of the Perceived Behavioral Control variable show a (t) value of 2.014 and a (p) value of 0.044. It can be seen that the t value is larger and the p value is smaller, and the value of the Subjective Norms variable is the same as the previous variable showing values ​​of 3.055(t) and 0.002( p), as well as the third variable Word Of Mouth with values ​​of 2.134(t) and 0.033(p).